Biblical mothers as images of the Church. Issue 1 (2nd January 2019) - Laato, Anni Maria
ABSTRACT: Among the many images and symbols of the Church which the church Fathers used, biblical mothers had an important role. Some of these images, such as Mary as an image of the Church, became widespread and have influenced later Christian theology and iconography. In this article, both the development and different applications of these images will be explored. How and to what purpose these images were used in the Early Church will also be studied. Among the topics dealt with by using these images were the origin, age, character and purpose of the Church, as well as its relation to several 'others' (the Jews, the schismatics and the heretics). In modern ecclesiological discussions, especially of Eve and Mary as images of the Church, the role of the Church in salvation, as well as the communal interpretation of biblical mothers, are relevant.